Structural and dielectric features of (Bi0.5Na0.5)1−xBaxTiO3 lead-free ferroelectric ceramics: An approach to the phase diagram - Moya, B. R. [UNESP]; Iglesias-Jaime, A. C.; Silva, A. C.; Peláiz-Barranco, A.; Guerra, J. D.S. (AIP Publishing, 2024)
(Bi0.5Na0.5)1−xBaxTiO3 lead-free ferroelectric ceramics were synthesized via the conventional solid-state reaction method. Structural and dielectric properties were investigated as a function of the doping concentration, considering x = 0, 2, 5, 8, 10, 12, 16, and 18 at. % Ba. The structural analyses were carried out from the x-ray diffraction technique, including the Rietveld refinement method, and Raman spectroscopy. Results confirmed the formation of the perovskite structure, revealing different crystalline symmetries, depending on the Ba2+ concentration: the single rhombohedral ferroelectric phase (R3c) for x = 0 and 2 at. %; coexistence of both rhombohedral ferroelectric (R3c) and tetragonal antiferroelectric (P4bm) phases for x = 5 at. % Ba; the single tetragonal antiferroelectric phase (P4bm) for x = 8 at. % Ba; coexistence of two tetragonal phases (antiferroelectric P4bm and ferroelectric P4mm) for x = 10 at. % Ba; and the single tetragonal ferroelectric phase (P4mm) for x = 12, 16, and 18 at. % Ba. The characteristics of the phases’ transition, investigated from dielectric analysis, revealed the presence of two dielectric anomalies, which indeed have been associated to different phases’ transitions, one of them showing relaxor-like characteristics. The obtained results offer new insights for a better understanding on the features of the phase diagram for the studied ceramic system, according to the different observed crystalline symmetries (ferroelectric and antiferroelectric) in a very wide doping concentration. In the light of the obtained results, a new phase diagram has been proposed considering a wider compositional range than those reported in the literature.